Access, fronthaul and backhaul networks for 5G & beyond - Imran, Muhammad Ali; Zaidi, Syed Ali Raza; Shakir, Muhammad Zeeshan (IET telecommunications series ;, 2017)
This book provides an overview from both academic and industrial stakeholders of innovative backhaul/fronthaul solutions, covering a wide spectrum of underlying themes ranging from the recent thrust in edge caching for backhaul relaxation to mmWave based fronthauling for radio access networks.